Handbook of methods and instrumentation in separation science - Wilson, Ian D.; Poole, Colin F. (Elsevier, 2009)
This handbook is directed to the needs of scientists requiring concise overviews and targeted summaries of the main methods employed for separations. It is a work derived from the successful Encyclopedia of Separation Science with a new focus on the fundamentals of methods and instrumentation employed in separations. In a single source it affords access to general background material to enable the professional to quickly assimilate, sort and interpret the dense information associated with a comprehensive literature search. One-stop source for i.
Keywords: Separation (Technology); elektronické knihy; electronic books